Fluoride Exposure and Probabilistic Health Risk Assessment Through Different Agricultural Food Crops From Fluoride Endemic Bankura and Purulia Districts of West Bengal, India - De, Ayan; Mridha, Deepanjan; Ray, Iravati; Joardar, Madhurima; Das, Antara; Chowdhury, Nilanjana Roy; Roychowdhury, Tarit (Frontiers in Environmental Science, 2021)
The present study investigates the magnitude of fluoride (F-) contamination in agricultural land soil and food crops from F- endemic regions of Bankura and Purulia districts in West Bengal. Mean fluoride level in agricultural soil was 114 ± 59 mg/kg (n = 41) and 126 ± 65 mg/kg (n = 47) in Bankura and Purulia district, respectively. Considering the food crops cultivated in Bankura (n = 79) and Purulia (n = 108), the mean fluoride concentration in non-leafy vegetables (18.1 ± 6.51 mg/kg and 15.6 ± 5.93 mg/kg) and leafy vegetables (12.8 ± 2.8 mg/kg and 18.4 ± 6.33 mg/kg) from the two studied districts was comparatively higher than the cereal (2 ± 1.05 mg/kg and 2.01 ± 1.01 mg/kg) and pulses (3.35 ± 1.42 mg/kg and 4.82 ± 1.19 mg/kg). The BCF values of fluoride in food crops (n = 27) from Bankura (range: 0.007-0.377) and Purulia (range: 0.005-0.319) were much lower compared to the optimum value of 1. Estimated daily intake (EDI) of fluoride was highest for children in both Bankura (EDIcumulative = 0.0291 mg/kg bw/day) and Purulia (EDIcumulative = 0.0326 mg/kg bw/day) among all the studied age groups. The non-leafy vegetables contributed highest exposure of fluoride (approximately 55.5%) to EDIcumulative among all the food crops. The uncertainty analysis for assessment of probabilistic health risk was carried out for all the studied age groups through hazard index (HI), total hazard index (THI) and life time non-carcinogenic risk (HILTNR). However, HI value was found <1 for all the age groups resulting no such kind of potential health risk of fluorosis through consumption of individual food crops and the trend of THI from all the food crops was found in the order of children > adults > adolescents > teenagers from both the districts. The life time non-carcinogenic risk (HILTNR) of fluoride with percentile doses from P5 to P95 (exploring model of Monte Carlo Simulation) in all the studied age groups (4-70 years) was found > 1 indicating that the inhabitants were more vulnerable for their total life time period of fluoride exposure through consumption of food crops.